Habits Die Hard: The Semiotics of Wolf Management in Finland - Hiedanpää, Juha (Recherches sémiotiques, 2021)
Finland has struggled to formulate and implement policies for the national grey wolf (Canis lupus) population. Institutional adjustments were undertaken to improve wolf protection and human–wolf coexistence, but the wolf population has decreased. This calls for an explanation. I will apply Charles S. Peirce’s concept of habits and his semiotic theory to understand why it so difficult to design and implement a workable wolf policy. I intertwine Peircean methodology with the ontology provided by ecological economics and the analytic epistemic tools by old (traditional) institutional economics. Institutions exist to serve human purposes, and the modification of institutional infrastructure affects how social-ecological functions can still bring absent features of policy and management into existence. I therefore explicate the semiotic interplay of policy signs, objects, and interpretants in wolf management adjustments and consequent outcomes. Finally, the difficulty of habit formation for coexistence will be discussed and policy advice given. La Finlande a eu du mal à formuler et à mettre en oeuvre des politiques concernant la population nationale de loups gris (Canis lupus). Des ajustements institutionnels ont été entrepris pour améliorer leur protection de même que la coexistence humain-loup. Malgré ces efforts, la population de loups a diminué. Cela appelle une explication. J’appliquerai le concept d’habitudes de Charles S. Peirce et sa théorie sémiotique pour comprendre pourquoi il est si difficile de concevoir et de mettre en oeuvre une politique viable concernant les loups. J’entremêle la méthodologie peircienne à l’ontologie fournie par l’économie écologique et les outils épistémiques analytiques de l’économie institutionnelle ancienne (traditionnelle). Les institutions existent pour servir des objectifs humains, et la modification de l’infrastructure institutionnelle affecte la façon dont les fonctions socio-écologiques peuvent encore faire exister des caractéristiques absentes de la politique et de la ...